2019
DOI: 10.13057/biodiv/d200708
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Using wildlife for local livelihood – Experiences from the Bird’s Head Peninsula, West Papua, Indonesia

Abstract: Abstract. Pattiselanno F, Apituley JRM, Arobaya AYS, Koibur JF. 2019. Short Communication: Using wildlife for local livelihood – Experiences from the Bird’s Head Peninsula, West Papua, Indonesia. Biodiversitas 20: 1839-1845. Wildlife products are valuable commodities, and wild meat is considered as premium value because it has a high value per unit weight compared with other forest products Wildlife products are commonly used for consumption purpose, generating household income and cultural reasons. Because cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 42 publications
2
20
0
1
Order By: Relevance
“…We have also found that increased connectivity via roads changes the orientation of local people using natural resources and forest products from subsistence towards market-based drivers. Thus in some parts of the Bird's Head Peninsula, selling wild meat (venison in this case), is an easy way to generate household income (Pattiselanno et al, 2019;2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also found that increased connectivity via roads changes the orientation of local people using natural resources and forest products from subsistence towards market-based drivers. Thus in some parts of the Bird's Head Peninsula, selling wild meat (venison in this case), is an easy way to generate household income (Pattiselanno et al, 2019;2020).…”
Section: Discussionmentioning
confidence: 99%
“…Motivations for hunting vary between sites (Pattiselanno et al, 2020;Pattiselanno et al, 2019;Pattiselanno & Koibur, 2018). In sites without road access, hunting is mostly conducted to obtain meat for family consumption, whereas hunting for trade is more common in sites with road access.…”
Section: The Link Between Roads and Indigenous Hunting In Tanah Papuamentioning
confidence: 99%
See 1 more Smart Citation
“…The wildlife trade can act as a valuable source of financial income for hunters, farmers, exporters, and vendors alike [ 33 , 34 , 35 ]. However, even if the intrinsic value of wildlife is discounted (i.e., the value that wildlife possesses in its own right, as opposed to the instrumental or “resource” value [ 36 ]), a painfully topical question is whether the income generated from the legal trade in wildlife (estimated to be worth billions of US dollars globally per year) offsets the full longer term economic costs of its operation.…”
Section: Risks Presented By the Wildlife Trade Are Manifold And Cmentioning
confidence: 99%
“…The area harbors biotic factors with high diversity of flora and fauna. However, only little has been published scientifically i.e., wildlife (Shaverdo et al 2016;Szczepański et al 2018;Kaiser et al 2019;Pattiselanno et al 2019) and vegetation (Heatubun 2002;Heatubun et al 2009Heatubun et al , 2013Maturbongs et al 2014Maturbongs et al , 2015Sillanpää et al 2017;Robiansyah 2018).…”
Section: Introductionmentioning
confidence: 99%